Service Delivery Mechanism on Content Based Cluster using Similarity of Services - Anitha, T.N; Balakrishna, R (Discoveries in Agriculture and Food Sciences, 2015)
Load balancing on web servers has become a major area of research due to ever increasing internet users’ population and heavy load on popular website servers. Content based load balancing is proved to be a good mechanism to balance load on servers providing high quality services to the users’ requesting for different category of content. On-demand creation of virtual servers has solved the complexity of load distribution and clusterization helps in grouping of same category servers. We propose a novel mechanism which works on clusterization of different grade servers intended to provide content based services to the users. Through experimental results it is found that this technique is helpful in increasing throughput and provides better quality of service to the users.